Best Practices in Ministry to Youth Navigating Gender Identity and Faith - Yarhouse, Mark A. (Christian education journal, 2021)
Gender identity has become an increasingly complex area of ministry with youth. Gender identity refers to a person’s experience of themselves as a boy or a girl or a different gender identity than that, such as transgender or one of several emerging gender identities. This paper will discuss transgender experiences, as well as more atypical experiences, to prepare those in youth ministry to provide more effective ministry to youth navigating gender identity and Christian faith.